1997
DOI: 10.1101/gr.7.12.1123
|View full text |Cite
|
Sign up to set email alerts
|

Zooming in on the Human–Mouse Comparative Map: Genome Conservation Re-examined on a High-Resolution Scale

Abstract: Over the past decade, conservation of genetic linkage groups has been shown in mammals and used to great advantage, fueling significant exchanges of gene mapping and functional information especially between the genomes of humans and mice. As human physical maps increase in resolution from chromosome bands to nucleotide sequence, comparative alignments of mouse and human regions have revealed striking similarities and surprising differences between the genomes of these two best-mapped mammalian species. Wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 74 publications
4
61
0
Order By: Relevance
“…Notwithstanding the high degree of conservation, the rearranged order of genes on the X chromosome suggests intrachromosomal rearrangements (Nadeau 1989;Farr and Goodfellow 1992). Recent studies showing over eight conserved Xchromosomal regions being rearranged between human and mouse (Blair et al 1994;Carver and Stubbs 1997), and an additional nine just within the distal 12 Mb of HSAXp22.3 (Blaschke and Rappold 1997), indicate a much more complex sequence of events leading to the divergent organization of the X chromosomes of these two species.…”
Section: Conservation Of Whole Chromosome Syntenymentioning
confidence: 99%
“…Notwithstanding the high degree of conservation, the rearranged order of genes on the X chromosome suggests intrachromosomal rearrangements (Nadeau 1989;Farr and Goodfellow 1992). Recent studies showing over eight conserved Xchromosomal regions being rearranged between human and mouse (Blair et al 1994;Carver and Stubbs 1997), and an additional nine just within the distal 12 Mb of HSAXp22.3 (Blaschke and Rappold 1997), indicate a much more complex sequence of events leading to the divergent organization of the X chromosomes of these two species.…”
Section: Conservation Of Whole Chromosome Syntenymentioning
confidence: 99%
“…In bacteria, long strings of genes show conserved order and orientation between closely related species or strains, so that most rearrangements involve large pieces of DNA (1)(2)(3)(4). Comparative genetic mapping in vertebrates and plants has shown that large syntenic regions are conserved, with breakpoints corresponding to interchromosomal translocations (5,6). More detailed mapping of some of these syntenic regions, however, has revealed several examples where the local gene order is not conserved (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Whereas both chromosome painting and somatic cell hybrid mapping represent complementary approaches to define interspecific homologous chromosome segments, neither addresses the problem of gene order within conserved syntenies. In-deed, the human/mouse comparison has demonstrated an unsuspected level of internal rearrangements in several occurrences (Carver and Stubbs 1997). Similarly, a few alterations in gene order have been described between ruminants and humans (see Barendse et al 1997;Sun et al 1997;Yang et al 1998), but data are very scarce at the wholegenome scale.…”
mentioning
confidence: 99%